Bearing capacity of a strip footing on a geosynthetic reinforced soil modular block walls after a seismic loading - Zerguine, Salah; Benmeddour, Djamel; Mabrouki, Abdelhak (Journal of Applied Engineering Science & Technology; Vol 4 No 1 (2018), 2018)
Geosynthetic reinforced walls are widely used in public works. The aim of this paper is to study the bearing capacity of a strip rough footing on a geosynthetic reinforced soil modular block walls, after a seismic action. The numerical modelling was carried out by using the finite element method implemented in the Plaxis code. The influence of the eccentric vertical load on the bearing capacity of footing was examined considering different distances between the top of the wall and the edge of the footing. The results of this study confirm that the seismic loading does not affect the bearing capacity when the distance d/B is greater than 10.